Linking Organizational Justice Dimensions and Turnover Intention: The Mediating Role of Work Stress - Dani Rizana; Irfan Helmy (Reviu Akuntansi, Manajemen, dan Bisnis, 2026)
Purpose: This study aims to examine the effects of organizational justice dimensions–distributive, procedural, and interactional justice–on turnover intention, with work stress acting as a mediating variable in the banking sector. Research methodology: A quantitative approach was employed using survey data collected from 134 employees of a rural credit bank in Central Java, Indonesia. The data were analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS) to test both direct and indirect relationships among the variables. Results: The findings revealed that distributive and interactional justice had significant negative effects on turnover intention, whereas procedural justice did not show a direct effect. All three dimensions of organizational justice significantly reduced work stress, which in turn had a positive and significant effect on turnover intention. Mediation analysis confirmed that work stress significantly mediated the relationships between distributive, procedural, and interactional justice and turnover intention. Conclusions: The results indicate that employees’ perceptions of fairness, particularly in outcome distribution and interpersonal treatment, play a critical role in reducing turnover intention, both directly and indirectly, through lower work stress. Limitations: This study is limited by its cross-sectional design and focus on a single rural banking institution in one province, which may restrict the generalizability of its findings. Contributions: This study contributes to the organizational justice literature by empirically demonstrating the mediating role of work stress in the justice–turnover relationship and provides practical insights for human resource management in banking organizations within developing countries.